Larger pain extent is associated with greater pain intensity and disability but not with general health status or psychosocial features in patients with cervical radiculopathy. Issue 8 (26th February 2021) - Lam, Kwun; Peolsson, Anneli; Soldini, Emiliano; Löfgren, Håkan; Wibault, Johanna; Dedering, Åsa; Öberg, Birgitta; Zsigmond, Peter; Barbero, Marco; Falla, Deborah
Abstract : Abstract: Pain as a result of cervical radiculopathy (CR) can be widespread, nondermatomal and individually specific, but the association between pain extent and other clinical features has never been explored. The objective of this study is to investigate whether pain extent relates to clinical variables including pain intensity in addition to health indicators including disability, general health, depression, somatic anxiety, coping strategies or self-efficacy. An observational cohort study was conducted. Participants were recruited from 4 hospital spinal centres in Sweden. Pain extent was quantified from the pain drawings of 190 individuals with cervical disc disease, verified with magnetic resonance imaging (MRI) and compatible with clinical findings (examined by a neurosurgeon), that show cervical nerve root compression. Pain extent was evaluated in relation to neck pain, arm pain, and headache intensity. Multiple linear regression analysis were then used to verify whether pain extent was associated with other health indicators including disability, health-related quality of life, depression, somatic anxiety, coping strategies and self-efficacy. Pain extent was directly related to neck, arm and headache pain intensity (all P < .01). Multiple linear regression revealed that pain extent was significantly associated only to the level of perceived disability ( P < .01). Increased pain extent in people with CR is associated with higher headache, neck and arm pain intensity, and disability but not measures of general health, depression, somatic anxiety, coping strategies or self-efficacy. Abstract : Supplemental Digital Content is available in the text